Attitudes and Knowledge of Diabetic Patients in Kirkuk Governorate - Yassen M. Mussa; Younis Khider Baez (Kufa Journal for Nursing Sciences)
Background : Diabetes mellitus (DM) is a very serious disease affecting people of varying age and race all over the world, it is a condition in which the body produces little or none of the hormone insulin. If left untreated, the blood glucose levels can rise to such a point as to cause coma or possibly even death.